If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+12+3x=5
We move all terms to the left:
9x+12+3x-(5)=0
We add all the numbers together, and all the variables
12x+7=0
We move all terms containing x to the left, all other terms to the right
12x=-7
x=-7/12
x=-7/12
| 4^x-5.2^x=-4 | | -6(3-6x)=-18+4x | | n2-2n+24= | | -33=m(-11) | | 2(4+x)=11-3x | | -3p=-4-3 | | Y+1=3y-5(y-2) | | 55=80.71x=458.55 | | -7-13a=-14 | | 125m-100m+38200=41000-175 | | 4w+10=2w | | 14=35a | | -2-7w=-8w-8 | | 12=6(2x-8) | | 3(x+5)=-2(3x+6) | | 15y=25 | | -2-w=-8w-8 | | 716=x+394 | | 6d−11/2=2d−13/2 | | 4w+12w=-10 | | 13-2x=-0.8 | | y/2+5=-9 | | 2w-4=2w-4-8 | | -3y+4=5(y-7) | | -4(2-x)+3x=12x+7 | | -39+a=7(4a+6) | | (7x+1)^2-17(7x+1)-60=0 | | -17+x=4x+1 | | 1/2(8a+12)-27=16 | | 3x-2+2x=18 | | -5(x+7)=-50 | | 3²+x²=12² |